2000
DOI: 10.1046/j.1365-2672.2000.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a water extract of Moringa oleifera seeds on the hydrolytic microbial species diversity of a UASB reactor treating domestic wastewater

Abstract: The effect of a continuous supply of a water extract of Moringa oleifera seeds (WEMOS) on the hydrolytic microbial population of biomass grown in mesophilic upflow anaerobic sludge blanket reactors treating domestic wastewater was investigated. The WEMOS‐treated sludge had seemingly a wider diversity, with enterobacter and klebsiella as dominant hydrolytic bacteria, compared with the control sludge. Additional tests indicated that various hydrolytic bacteria could degrade WEMOS. It appeared that a continuous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
2
15
1
1
Order By: Relevance
“…The nutritional properties of leaves and seeds of M. oleifera were shown by Sreelatha and Padma (2009) and Afuang et al (2003). Thirty-four diseases are treated with various products of M. oleifera, as shown by the works of several authors who provide a scientific basis of these uses (Anwar et al 2006, Anwar et al 2007, Ayanbimpe et al 2009, Beltrán-Heredia et al 2009, Gilani et al 1994, Kalogo et al 2000, Kumar et al 2007, Lea 2010. The massive use of leaves in human and animal nutrition and in traditional medicine implies premature and continuing harvests, which constitutes a pressure on the foliar biomass and consequently on the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional properties of leaves and seeds of M. oleifera were shown by Sreelatha and Padma (2009) and Afuang et al (2003). Thirty-four diseases are treated with various products of M. oleifera, as shown by the works of several authors who provide a scientific basis of these uses (Anwar et al 2006, Anwar et al 2007, Ayanbimpe et al 2009, Beltrán-Heredia et al 2009, Gilani et al 1994, Kalogo et al 2000, Kumar et al 2007, Lea 2010. The massive use of leaves in human and animal nutrition and in traditional medicine implies premature and continuing harvests, which constitutes a pressure on the foliar biomass and consequently on the species.…”
Section: Discussionmentioning
confidence: 99%
“…Antispasmodic activity and hypotensive components of M. oleifera provide a scientific basis for the plant's traditional uses in the management of gastro-intestinal motility disorders (Gilani et al 1994). Kalogo et al (2000) also indicated that antibacterial properties of M. oleifera make it a useful medicinal plant.…”
Section: Introductionmentioning
confidence: 99%
“…Crushed seeds are a viable replacement of synthetic coagulants (Kalogo et al, 2000). In Sudan, seed crude extract is used instead of alum by rural women to treat the highly turbid Nile water because of a traditional fear of alum causing gastrointestinal disturbances and Alzheimer's disease (Crapper et al, 1973;Miller et al, 1984;Martyn et al, 1989;Muyibi, 1994).…”
Section: Moringa Seeds As Coagulantmentioning
confidence: 99%
“…have reported its use as a coagulant (Jahn and Dirar, 1979;Muyibi and Evison, 1995;Jahn, 1986Jahn, , 1988Folkard et al, 1992); a softening agent (Muyibi et al, 2003); and a bactericidal agent (Madsen et al, 1987;Eilert et al, 1981;Kalogo et al, 2000). Thilza et al (2010) reported that Moringa leaf stalk extract had Afr.…”
Section: Introductionmentioning
confidence: 99%